(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2021)
Two archaeo-palaeontological Lower Pleistocene sites of Orce (Baza Basin, SE Spain), Fuente Nueva 3 (1.3 Ma) and Barranco León (1.4 Ma), preserve some of the earliest evidences of human presence in the European continent. During the 2013 field season, a small Lyncodontini mustelid mandible was found at Fuente Nueva-3. This finding was accompanied by a lower canine (c1), also from the same site, and a lower fourth premolar (p4) from Barranco León. Here, we report on the morphological and biometrical study of these materials, in comparison to other Eurasian Pliocene-Pleistocene species of the tribe Lyncodontini. The analyses revealed an affinity between the taxon from Fuente Nueva-3 and Barranco León with the small-sized European species Martellictis ardea (Gervais, 1848-1852), allowing us to ascribe the described material to the latter species. The presence of M. ardea in the sites of Orce is the southernmost occurrence of the species in the Iberian Peninsula and an important finding in the scarce fossil record of Lyncodontini in Europe.